(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article analyzes the application possibilities of the Python programming language in various fields, particularly in education, industry, oil and gas, and data science directions. Based on sources, the strategic role of Python language in programming culture, technological infrastructure, and information society is highlighted. The research substantiates the role of Python’s syntactic convenience, library ecosystem, and cross-platform adaptability in shaping it as a leading programming tool in the future.